2014
DOI: 10.15252/embr.201438534
|View full text |Cite
|
Sign up to set email alerts
|

SUMO 2 is essential while SUMO 3 is dispensable for mouse embryonic development

Abstract: Small ubiquitin-like modifier (SUMO1-3) conjugation plays a critical role in embryogenesis. Embryos deficient in the SUMO-conjugating enzyme Ubc9 die at the early postimplantation stage. ;Sumo3 +/À with Sumo3 À/À mice, and these rare mice were considerably smaller than littermates of the other genotypes. Thus, our findings suggest that expression levels and not functional differences between SUMO2 and SUMO3 are critical for normal embryogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
177
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 173 publications
(183 citation statements)
references
References 14 publications
6
177
0
Order By: Relevance
“…SUMO1 -/-mice are also viable and fertile and lack any obvious phenotype, indicating that the SUMO2 pool is able to compensate for the absence of SUMO1 [19,20]. Mating experiments between the different knockout mice further indicated that the different SUMO family members functionally compensated for each other [18]. Thus, accurate mouse development appears to require the presence of a critical level of SUMO2.…”
Section: Twenty Years Of Sumo Research In Cell Cycle Controlmentioning
confidence: 99%
See 3 more Smart Citations
“…SUMO1 -/-mice are also viable and fertile and lack any obvious phenotype, indicating that the SUMO2 pool is able to compensate for the absence of SUMO1 [19,20]. Mating experiments between the different knockout mice further indicated that the different SUMO family members functionally compensated for each other [18]. Thus, accurate mouse development appears to require the presence of a critical level of SUMO2.…”
Section: Twenty Years Of Sumo Research In Cell Cycle Controlmentioning
confidence: 99%
“…SUMO2 is the only essential SUMO family member. SUMO2-deficient mice died early during embryonic development (embryonic day 10.5), with severe developmental defects [18]. In contrast, SUMO3 -/-mice were viable and did not show any overt defects [18].…”
Section: Twenty Years Of Sumo Research In Cell Cycle Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…Like in every other cell type studied so far, SUMOylation substrates are dominantly found in the nucleus of neuronal cells, but some controversy exists regarding extranuclear substrates in general and synaptic substrates in particular (Daniel et al., 2017). Nevertheless, SUMOylation has attracted increasing interest in the field of neurosciences and has been shown to regulate neuronal function under physiological and pathophysiological conditions (Krumova & Weishaupt, 2013; Wang et al., 2014; Yang & Paschen, 2015). …”
Section: Introductionmentioning
confidence: 99%